A comparison between residual renal function and peritoneal clearance for Na/H2O and urea removal in peritoneal dialysis patients. (August 2014) - Shan, Yisheng; Xu, Feifei; Sun, Mei; Ji, Jun; Ding, Xiaoqiang
Abstract Background: To compare the Na/H2O and urea removal between residual renal function (RRF) and peritoneal clearance (PC) in peritoneal dialysis patients. Try to explore the difference between RRF and PC in prognosis of chronic kidney disease patients who need peritoneal dialysis (PD) treatment. Methods: Weekly Na/H2O and urea removal by PC and RRF were investigated individually. Independent samples t-test was carried out to compare the efficiency of removal between RRF and PC treatment. Pearson correlated analysis was applied to reveal the relationship between Na/H2O and urea removal and Kt/V. Results: Although a higher Na/H2O removal rate by RRF was showed in this investigation, the difference was not statistical significant compared to the one by PC. On the other hand, urea removal by RRF was obviously higher than PC. For every 0.1 Kt/V, Na/H2O removal by RRF was distinctly higher than PD. The Na and H2O removal of RRF were 147.88 ± 83.72 mmol and 46.54 ± 39.11 mmol, respectively; and the ones of PD were 11.40 ± 6.08 mmol and 4.47 ± 4.79 mmol. By using statistical assay, the correlations relevance between Na/H2O removal and Kt/V in RRF were showed stronger than in PC. However, the total removal of Na/H2O showed a poor correlation with Kt/V in both RRF and PC. Conclusions: The removal efficiency of RRF is much higher than PC. This study suggests that it is important to adjust dialysis program when RRF gets declined. Also the correlation between Na/H2O removal rate and Kt/V is an important monitoring factor for the patients who are receiving peritoneal dialysis.